“Voices in controversia”: review of Argentina experience revolutionary in mexican magazine (1979-1981) - Tortti, María Cristina (Revista de Historia Social y de las Mentalidades, 2024)
This paper aims to show the terms from which a group of Argentine intellectuals exiled in Mexico reflected on the failed revolutionary experience recently crushed in Argentina. With this aim in mind and with the conviction that the defeat was irreversible, this group agreed on the need to review the certainties on which that project had been based. Controversia thus became a space for debate in which the political rationality of the New Left was deconstructed, as many of the topics that would be discussed during the democratic transition were outlined.